Multiproxy stable isotope analysis provides insights into diet, animal management, and residential mobility in Old Bara, a metropolitan suburb of the Oyo Empire, West Africa - Moses Oluwaseyi Akogun; Paul Szpak; Vicky M. Oelze; Kendra Leishman; Jay Hilsden; Camilla Speller; Lisa Janz; Jonathan O. Aleru; Akinwumi Ogundiran (PLoS ONE, 2026)
Old Bara was a royal suburb in the metropolis of the Oyo Empire, one of the most important political entities in Africa, ca. 1600–1835. Much of what is known about this town is limited to a few written and oral accounts about its functions as a royal cemetery where the priests and priestesses of the deified kings and other dependents also resided. These limited sources suggest that as a secluded site, Old Bara depended on the palace for its provisions. Archaeological, zooarchaeological, and bioarchaeological research at Old Bara has opened the opportunity to answer new questions about Old Bara’s past and to evaluate its identity as a royal site. Here, we use carbon ( δ 13 C), nitrogen ( δ 15 N), sulfur ( δ 34 S), and strontium ( 87 Sr/ 86 Sr) isotope analysis coupled with zooarchaeology and Zooarchaeology by Mass Spectrometry (ZooMS) to investigate animal provisioning, diet, and residential mobility in Old Bara. Our data provide evidence for local management of animal resources, including the first evidence for horse breeding in the Oyo Empire. The study also challenges the historical accounts that Old Bara was home primarily to palace retirees and priests and priestesses who were required to be celibate and relied on the palace for food provisions. The cumulative evidence from the analyses indicates that the royal town was part of the empire’s animal resource production and distribution network.